Multicentre study of neoadjuvant chemotherapy for stage I and II oesophageal cancer. Issue 7 (4th April 2016) - Bekkar, S; Gronnier, C; Renaud, F; Duhamel, A; Pasquer, A; Théreaux, J; Gagnière, J; Meunier, B; Collet, D; Mariette, C; Dhahri, A; Lignier, D; et al.
Abstract: Background: The benefit of neoadjuvant chemotherapy (NCT) for early-stage oesophageal cancer is unknown. The aim of this study was to assess whether NCT improves the outcome of patients with stage I or II disease. Methods: Data were collected from 30 European centres from 2000 to 2010. Patients who received NCT for stage I or II oesophageal cancer were compared with patients who underwent primary surgery with regard to postoperative morbidity, mortality, and overall and disease-free survival. Propensity score matching was used to adjust for differences in baseline characteristics. Results: Of 1173 patients recruited (181 NCT, 992 primary surgery), 651 (55·5 per cent) had clinical stage I disease and 522 (44·5 per cent) had stage II disease. Comparisons of the NCT and primary surgery groups in the matched population (181 patients in each group) revealed in-hospital mortality rates of 4·4 and 5·5 per cent respectively ( P = 0·660), R0 resection rates of 91·7 and 86·7 per cent ( P = 0·338), 5-year overall survival rates of 47·7 and 38·6 per cent (hazard ratio (HR) 0·68, 95 per cent c.i. 0·49 to 0·93; P = 0·016), and 5-year disease-free survival rates of 44·9 and 36·1 per cent (HR 0·68, 0·50 to 0·93; P = 0·017). Conclusion: NCT was associated with better overall and disease-free survival in patients with stage I or II oesophageal cancer, without increasing postoperative morbidity. Abstract : Improves survival